The Impact of Fiscal Decentralization on Poverty Reduction in Vietnam - Pham, Thu Hang; Bui, Huy Nhuong; Do, Anh Duc; Le, Anh Duc; Ha, Dieu Linh; Ngo, Hai An (The Economics and Finance Letters, 2022)
In Vietnam, the issue of decentralization and implementation of decentralization have been a concern for a long time. This study focuses on the impact of fiscal decentralization on poverty reduction in Vietnam. Based on the provincial data with the use of the two-stage least squares method (2SLS), the estimation results obtained for the two periods show that fiscal decentralization had an impact on income/expenditure poverty reduction in the period from 2010–2015 and it had no significant effect on multidimensional poverty reduction in the period from 2016–2019. The study also found that economic growth, education and local welfare spending had an impact on poverty reduction in both stages, in which the impact of economic growth is relatively large, while the impact of welfare expenditures is relatively small in the locality. Improving infrastructure through information networks and increasing participation of people at the grassroots level have no impact on income/expenditure poverty reduction and multidimensional poverty in both the 2010–2015 and 2016–2019 periods.